Beyond Classical Fiqh: Sa'ad al-Dīn al-'Uthmānī's Ijtihādī Methodology in Islamic Constitutional Jurisprudence - Abdul Azis, Fakih; Az-Zuhri, Muhammad (Institut Agama Islam Negeri Kendari, 2026)
This article examines Sa'ad al-Dīn al-'Uthmānī's contribution to Islamic constitutional jurisprudence through qualitative, analytical-descriptive analysis of his books, peer-reviewed articles, and political speeches. The study addresses a significant research gap by moving beyond existing ideological critiques to systematically reconstruct his constitutional vision and its juristic foundations. Employing thematic coding, the research maps his arguments onto core dimensions of constitutional thought, including sources of political authority, the distinction between religious and political communities, and the protection of rights. The findings demonstrate that al-'Uthmānī rejects the notion of a fixed